Diverse Roles of Inhibitor of Differentiation 2 in Adaptive Immunity - Lucille Rankin; Gabrielle T. Belz (Clinical and Developmental Immunology)
The helix-loop-helix (HLH) transcription factor inhibitor of DNA binding 2 (Id2) has been implicated as a regulator of hematopoiesis and embryonic development. While its role in early lymphopoiesis has been well characterized, new roles in adaptive immune responses have recently been uncovered opening exciting new directions for investigation. In the innate immune system, Id2 is required for the development of mature natural killer (NK) cells, lymphoid tissue-inducer (LTi) cells, and the recently identified interleukin (IL)-22 secreting nonconventional innate lymphocytes found in the gut. In addition, Id2 has been implicated in the development of specific dendritic cell (DC) subsets, decisions determining the formation of αβ and γδ T-cell development, NK T-cell behaviour, and in the maintenance of effector and memory CD8+ T cells in peripheral tissues. Here, we review the current understanding of the role of Id2 in lymphopoiesis and in the development of the adaptive immune response required for maintaining immune homeostasis and immune protection.